Nanoemulsion-Based Technologies for Delivering Natural Plant-Based Antimicrobials in Foods - McClements, David Julian; Das, Arun K.; Dhar, Pubali; Nanda, Pramod Kumar; Chatterjee, Niloy (Frontiers in Sustainable Food Systems, 2021)
There is increasing interest in the use of natural preservatives (rather than synthetic ones) for maintaining the quality and safety of foods due to their perceived environmental and health benefits. In particular, plant-based antimicrobials are being employed to protect against microbial spoilage, thereby improving food safety, quality, and shelf-life. However, many natural antimicrobials cannot be utilized in their free form due to their chemical instability, poor dispersibility in food matrices, or unacceptable flavor profiles. For these reasons, encapsulation technologies, such as nanoemulsions, are being developed to overcome these hurdles. Indeed, encapsulation of plant-based preservatives can improve their handling and ease of use, as well as enhance their potency. This review highlights the various kinds of plant-based preservatives that are available for use in food applications. It then describes the methods available for forming nanoemulsions and shows how they can be used to encapsulate and deliver plant-based preservatives. Finally, potential applications of nano-emulsified plant-based preservatives for improving food quality and safety are demonstrated in the meat, fish, dairy, and fresh produce areas.